2017
DOI: 10.13189/ujar.2017.050509
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition, Polyphenol Content and Anti-inflammatory Properties of White and Pigmented Italian Rice Varieties

Abstract: Rice (Oryza sativa L.) is a major staple food for the majority of the world population. Grown and harvested as paddy, it is present on our tables as white rice (milled), brown rice (dehusked) or, after being subjected to thermal processes, as parboiled rice. Recently, pigmented varieties are also appreciated (red and black rice). In this study, we evaluated proximate composition, polyphenol content and anti-inflammatory properties of Italian pigmented rice varieties and bran as well as white rice in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Also, Petroni et al . () observed no growth effects on the macrophage cells with red and black rice extracts (125 μ m ). There is almost no information on the effects of soaked and germinated pigmented rice extracts on the viability and NO inhibition of the 264.7 RAW macrophage cells.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Also, Petroni et al . () observed no growth effects on the macrophage cells with red and black rice extracts (125 μ m ). There is almost no information on the effects of soaked and germinated pigmented rice extracts on the viability and NO inhibition of the 264.7 RAW macrophage cells.…”
Section: Resultsmentioning
confidence: 89%
“…The TPC, TFC and TCC observed in this study (1.46 ± 0.11, 2.23 ± 0.07 and 2.08 ± 0.09 mg BE/100 g) were higher than those reported by Petroni et al . () who compared bioactive components of black/purple, red and white rice varieties. In their study, they observed that the black rice exhibited higher values for bioactive components with TPC 678 mg GAE/100 g compared with red rice (372.7 mg GAE/100 g) and brown rice (30.5–101.3 mg GAE/100 g); TFC 300 mg QE/100 g compared to red rice (200 mg QE/100 g) and brown rice (<100 mg QE/100 g); TCC 232.8 μg/100 g compared to red rice (20.59 μg/100 g) with no carotenoid detected in brown rice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of extracts made from pigmented rice grain has shown that the phenolic compounds tocopherol and anthocyanin are efficient neutralizers of reactive oxygen species (Zhang et al, 2015;Ghasemzadeh et al, 2018), while animal tests have proven that these compounds are bioavailable (Tantipaiboonwong et al, 2017). Several studies have shown that the elevated anti-oxidation activity exhibited by pigmented rice grains (most markedly by black rice) can be used to mitigate the inflammatory response (Chakuton et al, 2012;Petroni et al, 2017).…”
Section: Anti-oxidant Activitymentioning
confidence: 99%